2017
DOI: 10.1055/s-0037-1603637
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Plane Corrections around the Knee

Abstract: Stability of the knee joint depends on soft tissues integrity and bony balance in the frontal and sagittal planes during gait. Although frontal plane imbalance is a well-known knee pathology, commonly treated by high tibial osteotomy, sagittal plane imbalance is less common, with fewer and more challenging surgical treatment options. The purpose of this review is to describe the biomechanical effects of sagittal knee imbalances and to outline the indications, techniques, and outcomes of sagittal knee osteotomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 56 publications
(71 reference statements)
1
36
0
2
Order By: Relevance
“…There are some technical notes and case reports on slope-correction osteotomy and revision ACLR, but the only case series available were published by Dejour et al, 5 who studied 9 cases, and Sonnery-Cottet et al, 30 who studied 5 cases. 4,6,16,30,35 In line with the studies by Dejour et al and Sonnery-Cottet et al, our study showed very good clinical results and few complications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There are some technical notes and case reports on slope-correction osteotomy and revision ACLR, but the only case series available were published by Dejour et al, 5 who studied 9 cases, and Sonnery-Cottet et al, 30 who studied 5 cases. 4,6,16,30,35 In line with the studies by Dejour et al and Sonnery-Cottet et al, our study showed very good clinical results and few complications.…”
Section: Discussionsupporting
confidence: 92%
“…Biomechanical studies have demonstrated that a high force on the ACL may contribute to ACLR failure. 17,38 There are a number of recommendations for surgically treating an elevated PTS in patients undergoing revision ACLR, 4,27,34 but a large case series has not been published to date.…”
mentioning
confidence: 99%
“…Anteroposterior knee laxity was assessed using ‘static’ and ‘dynamic’ measurements of anterior tibial translation (ATT) on ‘true lateral view’ radiographs, superimposing the posterior femoral condyles. The ATT was defined as the distance between two lines parallel to the posterior tibial cortex: the first tangent to the posterior aspect of the medial tibial plateau, and the second tangent to the posterior femoral condyles [ 12 , 35 ], Static ATT was measured on monopodal weight bearing radiographs with the knee flexed at 20°. Dynamic ATT was measured using the Telos™ stress radiography device (Metax, Hungen, Germany) with a constant anterior force of 150 N, and the side-to-side difference between the injured knee and healthy knee was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Today, the most established technique was described by Lecuire et al in 1980. 45,47,49,51,52 In so doing, the tibial tuberosity is detached first and fixed back after wedging, acting like a "bioplate. "…”
Section: Techniques Historical Aspectsmentioning
confidence: 99%